Implementasi QRIS sebagai Alternatif Pembayaran Non Tunai pada Kalangan Usaha Mikro, Kecil, dan Menengah (UMKM): Peluang dan Tantangan - Kristia, Erna; Arqy Ahmadi, Mirzam (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This study examines the QR Indonesian Standard or known as the Quick Response Code Indonesian Standard (QRIS) as one of the non-cash payment options available for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. This research method uses a qualitative method with a literature review technique, where researchers collect and analyze various relevant literature. The purpose of this study is to identify and analyze the opportunities and challenges for MSMEs in adopting QRIS for digital payments. In order to increase efficiency in transactions, open markets, and also facilitate access to financial services, Bank Indonesia has issued a QR code-based payment standard which is an opportunity for MSMEs. However, limited digital literacy, technological infrastructure, and resistance from business actors have hampered the implementation of QRIS. This study also discusses how government support and education can accelerate the adoption of QRIS to increase financial inclusion and the competitiveness of MSMEs in the digital era.